Creación del departamento de recurso humanos para la Empresa Piñas Ricas del Ecuador S.A "Pirecuasa", de la ciudad de Guayaquil - Parra Rocha, Mariuxi Ivonne (2011)
Rich Pineapple Company PIRECUASA del Ecuador SA, the city of Guayaquil Guayas province is a company that was created on September 19, 2000 by Mr. Michael Newman and Maurice Cohn Israeli and German nationality, at present this company dedicated to the purchase and sale of pineapples for export. But its hard to believe that this company with 11 years of creation does not have specific department or area to be responsible for the proper administrative management of human talent. To date management has-been. This was the main reason for which was raise day this research which conclude switch a proposal to create a human resources department tin the company. For the development of research focuses first the main problem is the lack of human resources department, establishing the effects that this causes problems such as miss management and causing problems inhuman talent. He focus don fulfilling the specific objectives1) to diagnose the current situation of human talent Rich Pineapple Company of Ecuador SA "PIRECUASA". 2) Determinethe organizational structure Ofthe Company’s Rich Piñas Ecuador S.A. "PIRECUASA 3) Develop aproposal for the creation of the human resources department of the company's Rich Piñas Ecuador SA" PIRECUASA". We conducted a survey of company employees in Ecuador Piñas PIRECUASA Richin order teethe administrative situation that owns this company and this is a lsointer viewed the CEO of the company to learn about how the administrative situation of the company. According to the statement byte employe eslearned that it is necessary and essential to create human resources department that will improve delivery subsystems, implementation, maintenance, development and control of personnel. The proposal to create the human resources department Pineapple Company PIRECUASA Ricas del Ecuador SA, has a technical, financial and human for its implementation. Functions and objectives were established for the department, as well as staff function sand contribute to the devel op ment of the company in the administrative. And finally it was learned that would impaction the authorities, using the creation of this department and this administration would contribute to the development of the company Piñas del Ecuador SA PIRECUASA Rich.